2018
DOI: 10.4103/ortho.ijortho_31_17
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Floating Knee Injury in Indian Population

Abstract: Background:Floating knee is a condition resulting from high energy trauma usually associated with minor to life threatening injuries making it challanging to treat There are no studies available in literature describing cross leg sitting and squatting after surgical management of floating knee. This study analyzes prognostic factors, plan of management, functional outcomes (special attention to squatting and cross legged sitting), complications.Materials and Methods:52 patients with floating knee injuries trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Studies reported mortality rate between 5% and 15% in patients with floating knee injuries which reflects the impact of associated injuries, 15 whereas in our study no mortality was reported. Goel et all in his study mentioned that left limb was more commonly involved than the right, another study done by Chavda AG et al showed right limb more commonly involved, 2,14 whereas in our study we found left limb to be more commonly involved, but the mechanism for limb preference in floating knee injuries was not explained in literature.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Studies reported mortality rate between 5% and 15% in patients with floating knee injuries which reflects the impact of associated injuries, 15 whereas in our study no mortality was reported. Goel et all in his study mentioned that left limb was more commonly involved than the right, another study done by Chavda AG et al showed right limb more commonly involved, 2,14 whereas in our study we found left limb to be more commonly involved, but the mechanism for limb preference in floating knee injuries was not explained in literature.…”
Section: Discussioncontrasting
confidence: 82%
“…In a recent study by Kao et al on floating knee injuries observed 26% were associated with head injury and 9% with abdominal or chest trauma and a similar study done in Gujarat by Chavda AG et al found 15% associated with head injury followed by 10% with chest trauma and 5% with abdominal injury. 13,14 Similarly in our study we found head injury is the most commonly associated injury which was seen in 12.5% of the subjects followed by and abdominal injuries which was seen in 8% of the patients with floating knee injuries. Studies reported mortality rate between 5% and 15% in patients with floating knee injuries which reflects the impact of associated injuries, 15 whereas in our study no mortality was reported.…”
Section: Discussionsupporting
confidence: 75%
“…Patients' follow-ups averaged 28 (14-70) months. Our comparison of hospital stay length between showed a mean length of 13.17 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) days in Group 1 and of 9.75 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days in Group 2. Length of stay showed a statistically significant difference between groups (p = 0.01).…”
Section: Resultsmentioning
confidence: 81%
“…Similar studies support the good outcomes of closed fractures. ( 12 Kulkarni et al ( 13 found that floating knee injuries suffer the influence of open or closed fractures, segmental nature, additional injuries, and intraarticular surfaces. Our study ignored floating knee injuries with segmental fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment typically involves immobilization with a brace or cast, nonweight-bearing or partial weight-bearing, and early mobilization as tolerated. Physical therapy and rehabilitation exercises are initiated to improve the range of motion, strengthen muscles, and facilitate functional recovery [35]. Close monitoring of clinical progress and serial imaging studies may be warranted to assess fracture healing and ensure the stability of the knee joint.…”
Section: Conservative Managementmentioning
confidence: 99%